2006
DOI: 10.1038/sj.ejcn.1602484
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in pregnancies of adolescents and mature women and the relationship to birth anthropometry

Abstract: Objective: To investigate differences in body composition between adolescent girls and mature women during pregnancy and the relationship to newborn anthropometry. Design: A prospective study. Setting: The antenatal clinic at the University Hospital of the West Indies, Kingston, Jamaica. Subjects: Four hundred and twenty-five women were invited to join the study. Three hundred and sixty-one women (84.9%) completed the study. Interventions: Study participants were divided into two groups: adolescents and mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 18 publications
0
43
1
Order By: Relevance
“…This lack has resulted in the frequent use of non-pregnancy-specific methods [22,23,24,25], which can reduce the validity of the results. …”
Section: Introductionmentioning
confidence: 99%
“…This lack has resulted in the frequent use of non-pregnancy-specific methods [22,23,24,25], which can reduce the validity of the results. …”
Section: Introductionmentioning
confidence: 99%
“…Whereas it is known that overnight-fasted, nonpregnant adolescent girls produce glucose at approximately the same rate as adults (11), it is not known whether adolescents can increase glucose production to the same extent as their adult counterparts during pregnancy. We (12) as well as others (13) have reported that pregnant adolescents gain more weight than do their adult counterparts during pregnancy. We also showed that most of this weight gain was in lean body mass (12), suggesting that pregnant adolescents may require more amino acids than adult women to support the increased protein synthesis associated with their own growth plus the growth of their reproductive tissues and fetus.…”
Section: Introductionmentioning
confidence: 49%
“…We (12) as well as others (13) have reported that pregnant adolescents gain more weight than do their adult counterparts during pregnancy. We also showed that most of this weight gain was in lean body mass (12), suggesting that pregnant adolescents may require more amino acids than adult women to support the increased protein synthesis associated with their own growth plus the growth of their reproductive tissues and fetus. Hence, as pregnancy progresses, unlike their adult counterparts, pregnant adolescents may not have sufficient gluconeogenic precursors to support increased gluconeogenesis.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…This increased weight gain was also seen in the current study, with the adolescents retaining more weight than the older women. An increase in gestational weight gain has been previously reported among adolescents and suggests that attainment of adequate weight and lean body mass in pregnancy impacts positively on birth size (29,32,33) .…”
Section: Discussionmentioning
confidence: 74%